A study of the three most common chromosome trisomies,21 (Down Syndrome), 18 (Edwards Syndrome) and 13 (Patau Syndrome) - Parrott, N,M. (My University, 1997)
In 1959 Lejeune and his colleague first demonstrated a chromosome abnormality and showed that " infant mongoliens " had 47 instead of the normal 46 chromosomes in their body cells. Recent studies show that about 1 in 200 infants have recognisable chromosome abnormalities.Trisomy 21 ( Down syndrome, DS ) trisomy 18 ( Edwards syndrome, ES ) and trisomy 13 ( Patau syndrome, PS ) have been found to be the most common trisomies with population incidences of approximately 1 in 650, 1 in 8000 and 1 in 10000, respectivevely.
A Research Report submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Science in Medicine. Johannesburg 1997.
Keywords: Trisomy; Chromosomes; Down Syndrome